Comprehensive review on various additive manufacturing techniques and its implementation in electronic devices. (January 2022) - Divakaran, Nidhin; Das, Jyoti Prakash; P V, Ajay Kumar; Mohanty, Smita; Ramadoss, Ananthakumar; Nayak, Sanjay Kumar
Graphical abstract: Highlights: 3D Printing possess the ability to fabricate complex structures with rapid prototyping for extensive applications in electronic devices. Various 3D printing techniques have been surveyed with a proper analysis on their pros and cons. The 3D printed structures have the tendency to overcome the challenges associated with their application in electronic and energy storage devices. This review provides an assessment on 3D printing as a tool for manufacturing cost-effective smart devices for industrial applications. Abstract: The recent advancement of science and technology in the world market has increased the demand for smart materials for various electronic device applications. The intrinsic challenges present in traditional manufacturing technologies in development of smart materials has enhanced the need to implement additive manufacturing techniques i.e., 3D printing (3DP) in electronic devices. The various 3DP techniques provide the designing freedom, innovation strategy, and minimization in waste with the capability to fabricate complex structures with rapid prototyping. The 3D printed structures have the tendency to overcome the challenges associated with their application in batteries, super capacitors, sensors and triboelectric nanogenerators (TENG) with excellent properties and output characteristics. The emergence of mechanical harvesting-based devices using 3DP has enhanced its versatility. The combination of burgeoning 3DP technology with advanced electronic devices has favoured the emergence of cutting-edge portable electronics with exceptional energy storage and internet of things. In this paper, an inclusive review of various 3DP techniques involved in electronic device application is carried out and the challenges involved in it have been addressed. The review focusses on the technical aspects of different 3DP techniques and their imperative role in manufacturing meticulous 3D printed structures for electronic devices. This paper also provides a summary of 3DP, as well as an assessment of its advantages and disadvantages, as a standard for future research and development in manufacturing cost-effective smart devices for industrial applications.